2g-11(-2)=26

Simple and best practice solution for 2g-11(-2)=26 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2g-11(-2)=26 equation:


Simplifying
2g + -11(-2) = 26

Multiply -11 * -2
2g + 22 = 26

Reorder the terms:
22 + 2g = 26

Solving
22 + 2g = 26

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Add '-22' to each side of the equation.
22 + -22 + 2g = 26 + -22

Combine like terms: 22 + -22 = 0
0 + 2g = 26 + -22
2g = 26 + -22

Combine like terms: 26 + -22 = 4
2g = 4

Divide each side by '2'.
g = 2

Simplifying
g = 2

See similar equations:

| 0=-6x-2x-8 | | Dy=Cx | | 4/3t=5/2 | | -6x-9+2x=39 | | (3t^2-t-4)(4t^2+3t-1)= | | 2x+5+3x=-25 | | 3(13+5.5k)=6k+18 | | 33=-4x-3x-2 | | -2-3x-4x=33 | | Cot^4x-1=0 | | 2-3x-4x=33 | | 2x^2+6y^2=13 | | 49/7p-49 | | 4[lnz+ln(z+5)]-2ln(z-5)= | | h=-16t*t+128t | | 4+6x+6x=-44 | | 1+7x+2x=109 | | 7(c-9)=9(2c-8)-4c | | 9x^6y^10/x^0Y^9 | | y=a^8+cos^8x | | n=c-m | | 3t+nt=y | | -4x+9+5x=18 | | 56=7/8v | | 10=(1/6)x | | 2x-5+5x=-54 | | 10p^3-25p^2+4p-10=0 | | y=4x^2-8 | | 2x-5+2x=23 | | (2x+5)x=420 | | 5x-6+5x=64 | | x-9+0.5=180 |

Equations solver categories